A Folha de S. Paulo e o governo Hugo Chávez: (2002-2005) - Salgado, Tiago Santos (2013)
The objective of this study is to determine how one of the three largest circulation national newspapers in Brazil Folha de S. Paulo covered Venezuela and President Hugo Chávez between the years 2002-2005. During this period Venezuela went through one of the most troubled times in its recent history with a coup in 2002, strikes, social demonstrations, recall referendums and the opposition refusal to participate in the legislative elections in 2005 facts that justify the attention given to the country by the communications media. In the development of this dissertation points pertinent to the methodology adopted and relevant historical aspects recovered from the trajectory of the newspaper Folha de S. Paulo are clarified within its chapters. A full background on recent Venezuelan history is seen, from the introduction of liberal democracy in the country in 1958, based on the role of traditional political parties such as Acción Democrática and COPEI and the agreement known as the Punto Fijo Pact, that was responsible for the adoption of neo-liberal policies that led to crises in the decades of the 1980s and 1990s and which resulted in the election of Hugo Chávez in 1998. Analysis is also seen of Folha de S. Paulo s editorial coverage in relation to the Venezuelan government and highlighting of the arguments that led this paper to consider it undemocratic, besides explaining the paper s understanding of democracy and how this could be linked to a liberal definition of the concept, as well as proceeding to an analysis of the Venezuelan opposition newspaper and the similarities between the coverage of Folha and that of private Venezuelan communication media against the government established by Chávez. In this way the analysis recurs to the interwoven critique of Hugo Chávez and the construction of his images as a populist leader a concept that became the subject of considerable historical discussion, bearing negative value from the links of his profile as a politician who deceived and manipulated the populace. Thus, we have aimed at a critical look at the concepts used by the Folha de S. Paulo to explain the nature of the Chávez government, beginning with data of the Venezuelan social reality that could explain the nature of the Chávez government and how it became possible to identify the ideology propagated by the Brazilian newspaper recovered from identification of the social function to which it complies as a vehicle of the major press and media and its influence in shaping Brazilian public opinion in relation to its neighboring country